Islamophobia and Muslim minorities in post 9/11 women’s fiction - Raihanah M.M.,; Ruzy Suliza Hashim,; Noraini Md Yusof, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
The bombings of the world trade towers in New York on the 11th of September 2001 dramatically changed the landscape of the west-east relations into blatant binary opposites of us and them. Within the western hemisphere, the repercussions of the 9/11 continue to be felt by minority Muslim communities living within the larger non-Muslim mainstream society such as America and Britain. The heightened tension has escalated into a new discourse termed Islamophobia causing Islam to be regarded as “a source of intolerance, extremism and terrorism, one whose adherents are out to destroy Western values.” Muslims living in the west, especially those who overtly exercise their religious sensibilities, be that in the form of the hijab for women or beard for men, bear the brunt of xenophobia exhibited by the mainstream society. This panel presentation sets out to address the issue of Islamophobia in fiction. The main premise of the presentation is to problematise the experience of being a Muslim minority as narrated in post 9/11 fiction by women. How did the 9/11 bombings affect the Muslim’s sense of reality as a member of religious and cultural minority? What multifaceted realities are Muslims in the west, be that born Muslims or reverts, exposed to? These issues will be examined based on the selected fiction by Muslim women writers in America and Britain.